2021
DOI: 10.1016/j.amsu.2021.102720
|View full text |Cite
|
Sign up to set email alerts
|

Unusual histopathological findings in appendectomy specimens with clinical diagnosis of acute appendicitis: A retrospective cohort analysis

Abstract: Introduction While appendicitis is considered one of most common acute surgical conditions, several studies have reported abnormal histopathological findings in appendectomy specimens; however, sending all appendices to histopathology is not yet routinely done.Here we report many unusual findings. Those unusual findings played a role not only in confirming acute appendicitis as a cause of the presentation in some cases but also discovering etiologies that mimic it with great impact on its manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…Earlier reports of E. vermicularis incidence in appendectomy specimens were ranged from 0.2% to 41.8%. 7 Enterobius vermicularis was found in 3 cases in the present study and nobody had acuteappendicitis on histology.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Earlier reports of E. vermicularis incidence in appendectomy specimens were ranged from 0.2% to 41.8%. 7 Enterobius vermicularis was found in 3 cases in the present study and nobody had acuteappendicitis on histology.…”
Section: Discussionsupporting
confidence: 39%
“…Malignant tumors of the appendix are carcinoids, mucoceles and adenocarcinomas. In this study, seven (7) cases with neoplasm in appendix were observed.…”
Section: Discussionmentioning
confidence: 81%
“…And the second one, the prolonged exposure and stimulus from carcinogens in the mucosal layer affecting different regions of adjacent tissue and promoting the coexistence of two or more distinct neoplasms. This latter theory could be more significant in the appendix as the appendix is a tubular structure with a blind end which would facilitate a prolonged exposure to retained intestinal carcinogens [4] [12] [13].…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal neoplasms are uncommon, representing less than 0.5% to 1% of all gastrointestinal tumors [1]. Appendix tumors include a heterogenous group of epithelial and nonepithelial neoplasms with the 2 main histopathologic types being, 1) neuroendocrine tumors (NETs) in 0.3% -0.9% of appendectomies, followed by 2) epithelial neoplasms, in 0.2% -0.3%, according to incidence reports [2] [3] [4]. Other rare neoplasms may be found, including an atypical hybrid tumor known as goblet cell carcinoma (formerly known as goblet cell carcinoids), which accounts for less than 5% of all appendiceal primary tumors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a thorough clinicopathological evaluation of the appendix is necessary for diagnosis, adequate management and follow-up. 1 2 3 4…”
mentioning
confidence: 99%